(untitled) (The Peerian Journal, 2025)
This study uses partial least squares structural equation modeling (PLS-SEM) to examine how customer experience affects medical tourism marketing. Methodology: The study looks at how visitor contentment, service quality, amenities, and environmental security affect visitor loyalty and satisfaction in the medical tourism industry. The study’s basic data came from a questionnaire given to 580 foreign visitors who came to Karbala for medical care. The data was examined using the researcher’s structural equation modeling (SEM) program, Smart PLS 3.0. According to statistical analysis, patient visits to private hospitals in Karbala are influenced by service quality, while tourist satisfaction is the main factor influencing loyalty. The marketing and operational divisions must work together to implement these suggestions, and the outcomes must be tracked using transparent performance metrics